FAMILY, SCHOOL, AND COMMUNITY COOPERATION IN DEVELOPING PARENTS’ PEDAGOGICAL CULTURE - Azimova Sayyora Toshtemirovna (Bright Mind Publishing, 2025)
The article analyzes the importance, main directions, and mechanisms of cooperation between the school, mahalla, and family in the formation and development of the pedagogical culture of parents. The study highlights the concept of pedagogical culture, its components, strategies for the effective organization of cooperation, and expected results.
Keywords: Pedagogical culture, family, school, mahalla, cooperation, upbringing, parental competence, communicative skills.